2010
DOI: 10.1177/0886260510370592
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparities in Arrest Outcomes for Domestic Violence

Abstract: Domestic violence arrests have been historically focused on protecting women and children from abusive men. Arrest patterns continue to reflect this bias with more men arrested for domestic violence compared to women. Such potential gender variations in arrest patterns pave the way to the investigation of disparities by sex of the offender in domestic violence arrests. This study utilizes data from a quantitative dataset that includes responses by police officers who completed a specially mandated checklist af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 32 publications
12
59
1
Order By: Relevance
“…This finding mirrors the seeming contradiction identified in previous research, that while people may view alcohol as a ‘cause’ of violence, they do not view it as an ‘excuse’[19,28,29]. And, although this one study from one area of Paris does not necessarily reflect responses by the correctional system in other parts of the world, a recent study in the USA [30] found similar results, with suspects in domestic violence interventions by police more likely to be arrested if they had been drinking, controlling for other factors such as injury of the victim, the presence of weapons and hostility of the suspect. These studies suggest that recognition of alcohol's role in intimate partner violence may lead to more serious consequences for offenders.…”
Section: The Role Of Alcohol At the Individual Level: Partner And Sexsupporting
confidence: 83%
“…This finding mirrors the seeming contradiction identified in previous research, that while people may view alcohol as a ‘cause’ of violence, they do not view it as an ‘excuse’[19,28,29]. And, although this one study from one area of Paris does not necessarily reflect responses by the correctional system in other parts of the world, a recent study in the USA [30] found similar results, with suspects in domestic violence interventions by police more likely to be arrested if they had been drinking, controlling for other factors such as injury of the victim, the presence of weapons and hostility of the suspect. These studies suggest that recognition of alcohol's role in intimate partner violence may lead to more serious consequences for offenders.…”
Section: The Role Of Alcohol At the Individual Level: Partner And Sexsupporting
confidence: 83%
“…The prediction of recidivism by offenders who assault same-sex partners also requires attention, and identifying a sufficient number of cases in this subgroup of offenders might require especially large cohort studies or case control designs (e.g., Glass et al, 2008). Because rates of recidivism can be expected to vary as a function of sample selection and outcome definition (e.g., Hanson, Helmus, & Thornton, 2010), larger samples will also be required to develop an experience table to afford norms specifically for female offenders and to explore how modifications to standard ODARA scoring might improve accuracy for women (e.g., Moons, Altman, Vergouwe, & Royston, 2009). Nevertheless, the present findings suggested that the ODARA is a valid measure of relative risk, which is arguably the most essential assessment matter because it shows how the assessed individual compares to the population of interest (e.g., Crawford & Garthwaite, 2009;Hanson, Lloyd, Helmus, & Thornton, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most robust and consistent predictors of arrest in IPV incidents included the presence of a weapon (Dichter et al, 2011; Durfee & Fetzer, 2016; Eigenberg et al, 1996; Eitle, 2005; Hamilton & Worthen, 2011), victim injury (Bachman & Coker, 1995; Buzawa & Austin, 1993; Dichter et al, 2011; Durfee & Fetzer, 2016; Eitle, 2005; Hamilton & Worthen, 2011; Robinson & Chandek, 2000; Tatum & Pence, 2015), presence of witnesses (Buzawa & Austin, 1993; Eigenberg et al, 1996; Hamilton & Worthen, 2011; Robinson & Chandek, 2000), and victim preference (Buzawa & Austin, 1993; Eigenberg et al, 1996). Extralegal factors, such as alcohol involvement, have also predicted arrest (Dichter et al, 2011; Durfee & Fetzer, 2016; Hamilton & Worthen, 2011; Roark, 2016). In terms of race/ethnicity, some studies have demonstrated that arrest has increased in IPV incidents involving White victims when compared with other racial/ethnic groups (Dichter et al, 2011; Eitle, 2005; Hamilton & Worthen, 2011; McCormack & Hirschel, 2018).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%